Availability study of palm oil mill / Mustafa Mohd Amin - Mohd Amin, Mustafa (1993)
The first law analysis provides an indication of the system performance whilst the second law analysis would pinpoint, the losses of the system as well the efficiency of the component in the system. The methodology, which employ both the first and second laws is identify here as Availability Analysis. In the view of waste in many common processes and practices in the industries, there is a reason for optimism that improving in energy utilization is possible. Improved utilization can come with reduction of available destruction within a device or process or with lessening of losses.